Anything new in the Miracle Report? Yes and No. - YANAGIHARA, Toru (1994)
Compares East Asian Miracle (EAM) with World Development Report 1991 (WDR). Concludes that (a) EAM's claim that selective intervention has not significantly affected sectoral growth patterns is not well substantiated; and (b) the report's conclusion that sectoral composition did not affect the overall rate of productivity growth, although technically correct, is only as good as the underlying assumptions. Presents possible alternative ways of conceptualizing the development process.